Transcriptome - wide bioinformatics analysis of the binding sites of RNA - binding proteins and their putative role in mendelian diseases - Phan, Nguyen Anh Thu; Matteo, Floris; Maria, Laura Idda; Nguyen, Hoang Bach (Tạp chí Y Dược Huế, 2022)
Background: Post-transcriptional regulation is the control of gene expression at the RNA level. After produced, the stability and distribution of the different transcripts are regulated by means of RNA-binding proteins (RBPs). Mutations in RNA-binding proteins can cause Mendelian diseases - prominently neuro- muscular disorders and cancers. This study determines the interaction between RBPs and target-RNA complexes from public data of the ENCODE project and identifies mutations associated with Mendelian diseases that could disrupt the RBP-RNA interactions. Materials and methods: we performed a transcriptome - wide bioinformatics prediction of the binding sites of RBPs in the human transcriptome from public data of the ENCODE project. Results: The majority (54%) of pathogenic mutation putatively affecting the binding sites of RBPs are located in protein - coding genes and are mainly classified as loss - of - function mutations. Mutations located in the binding sites of RBPs related to RNA processing. For 13 diseases, Familial hypercholesterolemia is the most significant disease with about 40% of mutations in ClinVar database located into the binding sites of RBPs (p=2.3e-65), but congenital hypogonadotropic hypogonadism is the disease with the highest percentage of mutations affecting the binding sites of RBPs (98%, p=2.7e-25). The RBPs most involved in human Mendelian diseases by binding sites-disrupting mutations are YBX3, AQR and PRPF8. Conclusions: A large number of Mendelian diseases are potentially mediated by disease - causing variants that potentially disrupt the binding sites of RBPs. This will provide insight sharper on post - transcriptional mechanisms. Besides, it is useful to know the role of protein - RNA interactome networks in pathologies, thereby serving the treatment of diseases.